Scheduling tank container movements for chemical logistics - Abdullah, Muhammed Hichael (2010)
Tank containers are widely used in the transport of fluid chemicals due to advantages in cost, safety, reliability and convenience over its alternatives. Logistics costs associated with tank container movements in the chemical industry is becoming increasingly important as the transport of fluid chemicals rely heavily on tank containers. As a result, it is essential to minimize the logistics costs in tank container movements, with certain areas of focus, like container flow imbalances and container cleaning. This project will present an event-based, “pull” approach, novel linear programming formulation to provide a minimum-cost or maximum-profit scheduling of container movements based on a set of given shipment orders. The formulation is applied to realistic and relevant examples to address issues such as intermodal transport and delivery time windows. The results obtained are compared to a similar study by Karimi et al1 and improvements to the formulation are proposed. The project also provides an introduction to chemical logistics and supply chain management, in which the use tank containers plays a major role, especially in the transport of fluid chemicals. The major issues, problems and considerations involved in supply chain management are highlighted and discussed.